Boosting the electrical conductivity of polymer matrix composites using low resistivity Z-filaments. (October 2020) - Abbasi, S.; Ladani, R.B.; Wang, C.H.; Mouritz, A.P.
Abstract: Fibre reinforced polymer laminates have low electrical conductivity compared to metals due to the high resistivity of the matrix phase, fibre-matrix interface, and fibres. This paper presents a new method for improving the electrical conductivity of fibre-polymer composites by through-thickness weaving of continuous filaments with high electrical conductivity (e.g. copper and other materials). Experimental testing and analytical modelling reveal that orthogonally weaving of conductive z-filaments in the through-thickness direction of carbon-epoxy composite increases the electrical conductivity by creating interconnected pathways for current flow. In particular, it is possible to increase the electrical conductivity by over two to three orders of magnitude by using a very low volume fraction (under 1.3 vol%) of metal z-filaments with a diameter of 0.51 mm. The improvements to both the in-plane and through-thickness electrical conductivities can be designed by controlling the volume fraction and by the judicious choice of the z-filament material. Graphical abstract: Unlabelled Image Highlights: A novel method for improving the electrical conductivity of fibre-polymer composites using woven metal z-filaments is presented. An analytical model is presented for computing the anisotropic electrical conductivities of the 3D-woven composites. Results reveal that a very low volume fraction ( 1.3 vol%) of metal z-filaments increase the electrical conductivity by over three orders of magnitude. The analytical model can be used to design 3D-woven composites with tailored electrical properties.